Dinamika pemaknaan pada arsitektur masjid: Telaah terhadap masjid tua dan masjid modern di Jawa Barat - Indri Astrina Fitria Indrarani Wirakusumah (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Humans are homo religiosus with a natural desire that there is an absolute power beyond reasoning which makes them "existent". This is observed from their religious behaviors as well as the continuous increase in their spirituality. Humans have a basic need to worship according to their religious orders and the construction of mosques is considered the fulfillment of the main needs of Muslims to conduct their prayers. The diversity of mosque forms in West Java showed that there is a mutually influencing relationship between the basic need for space to accommodate prayer rituals which tend to be dogmatic and the human desire to appreciate architectural elements of mosques as a form of contextual and dynamic spirituality enhancement. The comparison between the needs and desires in mosque architecture as indicated in previous studies was used as the main reference to understand the dynamics of the meaning in mosque architecture in order to produce new meaning reading diagrams. This was achieved through three main stages with the first being the re-description of the ideograms and typograms pairing in each mosque from the previous studies, the second is the identification of keywords that form the basis of thought for architects, users, and organizers as a series of triangulation processes to reveal new meanings and functions in the case study of mosques, and the third is the placement of the results of the analysis on the Function-Form-Meaning diagram to produce a new meaning reading diagram to identify the dynamics of meaning in mosque architecture in West Java. The contribution of this study is to enrich the theory and method of the meaning process in mosque architecture as well as to serve as a guide for architectural practitioners in designing mosques.